Parallel approach of a bioinspired routing protocol for MANETs. (4th March 2013) - Villalba, Luis Javier García; Cañas, Delfín Rupérez; Orozco, Ana Lucila Sandoval
Designing routing protocols for Mobile Ad Hoc Networks (MANETs) is a complex task because of its dynamic topology. A kind of routing protocols that suits the particularity of MANETs is so–called bio–inspired. Among these, focused on Ant Colony Optimisation (ACO), which studies the behaviour of ants in their search for food, are especially relevant. One of these algorithms is AntOR, which relying on swarm intelligence, efficiently solves routing in MANETs. In this paper we show a parallelised version of AntOR, the so–called P–AntOR, that using programming multiprocessor architectures based on shared memory protocol, allows to run tasks in parallel using threads, being applicable this parallelisation in the route discovery phase, route local repair process and link failure notification. The simulation results indicate that P–AntOR performs better than its predecessor, with emphasis on the metric of average End–To–End delay, jitter and packet delivery ratio.